2004
DOI: 10.1007/s10384-003-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COL8A2 Gene Mutation in Japanese Patients with Fuchs’ Endothelial Dystrophy and Posterior Polymorphous Dystrophy

Abstract: The R155Q and T502M mutations of COL8A2 may not be the causative defect in the Japanese FECD and PPMD patients examined in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…8,10,11 On the basis of studies reporting significant linkage of FECD, several pathogenic mutations in the collagen type VIII a2 gene (COL8A2), located on 1p34.3-p32, have been detected in affected individuals with FECD, and a strong association between FECD patients and genetic variants of COL8A2 has been validated by multiple studies. [6][7][8]12 In particular, two missense mutations, L450W and Q455K, showed perfect concordance in an FECD family having early onset and are positioned within the triple-helical domain of a2 collagen type VIII, which leads to the structural alteration of Descemet's membrane. 6,8,13,14 Also, in English FECD patients, three missense mutations of the COL8A2 gene, R155Q, R304Q, and R434H, were identified in familial and unrelated forms of common FECD, 8 whereas Aldave et al (2006) and Kobayashi et al (2004) reported that no COL8A2 variants associated with the common FECD subtype, late-onset FECD have been identified.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…8,10,11 On the basis of studies reporting significant linkage of FECD, several pathogenic mutations in the collagen type VIII a2 gene (COL8A2), located on 1p34.3-p32, have been detected in affected individuals with FECD, and a strong association between FECD patients and genetic variants of COL8A2 has been validated by multiple studies. [6][7][8]12 In particular, two missense mutations, L450W and Q455K, showed perfect concordance in an FECD family having early onset and are positioned within the triple-helical domain of a2 collagen type VIII, which leads to the structural alteration of Descemet's membrane. 6,8,13,14 Also, in English FECD patients, three missense mutations of the COL8A2 gene, R155Q, R304Q, and R434H, were identified in familial and unrelated forms of common FECD, 8 whereas Aldave et al (2006) and Kobayashi et al (2004) reported that no COL8A2 variants associated with the common FECD subtype, late-onset FECD have been identified.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8]12 In particular, two missense mutations, L450W and Q455K, showed perfect concordance in an FECD family having early onset and are positioned within the triple-helical domain of a2 collagen type VIII, which leads to the structural alteration of Descemet's membrane. 6,8,13,14 Also, in English FECD patients, three missense mutations of the COL8A2 gene, R155Q, R304Q, and R434H, were identified in familial and unrelated forms of common FECD, 8 whereas Aldave et al (2006) and Kobayashi et al (2004) reported that no COL8A2 variants associated with the common FECD subtype, late-onset FECD have been identified. 15 Furthermore, an observed association between the COL8A2 gene variants and FECD, as well as other corneal diseases, including keratoconus and posterior polymorphous corneal dystrophy (PPCD), was reported by others.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Linkage studies of large multigenerational families with late-onset FECD identified several chromosomal regions on chromosomes 1, 5, 8 and X to be associated with the disease (Sundin et al 2006a, b;Afshari et al 2009). A strong association between FECD and genetic variants of the COL8A2 (collagen type VIII α2) gene was reported (Biswas et al 2001;Kobayashi et al 2004;Gottsch et al 2005).…”
Section: Introductionmentioning
confidence: 99%